Comments on “An improved model for vehicle routing problem with time constraint based on genetic algorithm” [Comput. Ind. Eng. 42 (2002) 361–369] - Lei, Hong-Tao; Guo, Bo (Computers & industrial engineering, 2010)
An improved model for vehicle routing problem proposed by Heung-Suk Hwang (2002) was recently published in Computer & Industrial Engineering Journal to solve the time constraint vehicle routing problem based on improved genetic algorithm. In this work, comments are given to the published paper of Heung-Suk Hwang (2002). And they centralize on the example of improved mutation operator and the problem formulation. The suggested modifications are also provided in this work.